Dysfunction of 67-kDa Laminin Receptor Disrupts BBB Integrity via Impaired Dystrophin/AQP4 Complex and p38 MAPK/VEGF Activation Following Status Epilepticus - Park, Hana; Choi, Seo-Hyeon; Kong, Min-Jeong; Kang, Tae-Cheon (Frontiers in Cellular Neuroscience, 2019)
Status epilepticus (SE, a prolonged seizure activity) impairs brain-blood barrier (BBB) integrity, which results in secondary complications following SE. The non-integrin 67-kDa laminin receptor (67-kDa LR) plays a role in cell adherence to laminin (a major glycoprotein component in basement membrane), and participates laminin-mediated signaling pathways including p38 mitogen-activated protein kinase (p38 MAPK). Thus, we investigated the role of 67-kDa LR in SE-induced vasogenic edema formation in the rat piriform cortex (PC). SE diminished 67-kDa LR expression, but increased laminin expression, in endothelial cells accompanied by the reduced SMI-71 (a rat BBB barrier marker) expression. Astroglial 67-kDa LR expression was also reduced in the PC due to massive astroglial loss. 67-kDa LR neutralization led to serum extravasation in the PC concomitant with the reduced SMI-71 expression. 67-kDa LR neutralization also decreased expressions of dystrophin and aquaporin-4 (AQP4). In addition, it increased p38 MAPK phosphorylation and expressions of vascular endothelial growth factor (VEGF), laminin and endothelial nitric oxide synthase (eNOS), which were abrogated by SB202190, a p38 MAPK inhibitor. Therefore, our findings indicate that 67-kDa LR dysfunction may disrupt dystrophin-AQP4 complex, which would evoke vasogenic edema formation and subsequent laminin over-expression via activating p38 MAPK/VEGF axis.